2004
DOI: 10.1161/01.hyp.0000107778.85528.b5
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyoleic Acid

Abstract: Abstract-Recent studies have shown that diets rich in monounsaturated fatty acids (MUFAs) from olive oil, a natural source of oleic acid, have beneficial effects on blood pressure (BP) in hypertensive patients. With this in mind, we investigated whether a synthetic derivative of the MUFA oleic acid, 2-hydroxyoleic acid (2-OHOA), was capable of regulating the BP of Sprague-Dawley rats. Intraperitoneal and oral administration of 2-OHOA to rats induced significant and sustained decreases in BP in a time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Sprague-Dowley rats were used because they constitute a valuable model with little variability, appropriate to study the regulatory effects of fatty acids on BP (18). On the other hand, SHR is a well known model of hypertension (19), used in the present work to determine whether VOO might be useful to control high BP in human hypertensive subjects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sprague-Dowley rats were used because they constitute a valuable model with little variability, appropriate to study the regulatory effects of fatty acids on BP (18). On the other hand, SHR is a well known model of hypertension (19), used in the present work to determine whether VOO might be useful to control high BP in human hypertensive subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Solid lines represent the regression of the correlations, whose correlation coefficients (r) and statistical significance (P) are shown in both cases. chronic treatments as described (18). The polyclonal antisera against G␣i3 and G␣q/11 were obtained from Santa Cruz Biotecnology and that against G␣i2 was from PerkinElmer, and the anti-PLC␤1 antiserum was from BD Biosciences/ Transduction Laboratories.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we have recently demonstrated that an enhancement of the cAMP/PKA pathway in vascular tissue is responsible for the reduction of blood pressure observed in spontaneously hypertensive and normotensive SpragueDawley rats after 2-OHOA treatment. 11,33 In contrast, expression of COX8H and phosphorylation of CREB in rats treated with oleic acid declined to less than half of the levels of vehicle-treated control rats. This suggests that the high efficiency of 2-OHOA in the reduction of body weight is not caused by a simple potentiation of the activity of oleic acid but by a completely distinct mechanism.…”
Section: Effect Of C18 Fatty Acids On Body Weight O Vögler Et Almentioning
confidence: 98%